PENGARUH RETURN ON ASSET, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA: STUDI PADA PERUSAHAAN SEKTOR PERTAMBANGAN TAHUN 2019-2022 - Najibullah; Chairul Nisa; Lisnawati (JURNAL KREASI RAKYAT, 2024)
This research aims to determine the effect of return on asset, leverage, and firm size on tax avoidance in mining sector companies in 2019-2022. This type of research is quantitive with a population of 63 mining sector companies listed on the Indonesian Stock Exchange in 2019-2022.  The research sample was determined using a purposive sampling method so that 108 companies from the 27 mining sectors were obtained. Then, the sample data is analyzed using panel data regression. The random effect model is chosen based on the Hausman test and the Breush-Pagan Lagrangian Multiplier test for a random effect. The research results show that partial return on the asset has a negative and significant effect on tax avoidance, leverage which is measured by debt to equity ratio has a positive and significant effect on tax avoidance and a firm’s size has a negative but insignificant effect on tax avoidance. Simultaneously the variables return on asset, leverage, and firm’s size have a significant impact on tax avoidance.